2022
DOI: 10.24198/jkg.v34i3.42838
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Karakteristik fraktur palatum yang disertai fraktur dentoalveolar pada pasien trauma maksilofasial</p></strong><p><em><strong>Characteristics of palate fracture accompanied with dentoalveolar fracture in patients with maxillofacial trauma</p></em><strong>

Abstract: Fraktur palatum pada trauma maksilofasial jarang terjadi dan seringkali disertai fraktur dentoalveolar. Fraktur palatum yang disertai fraktur dentoalveolar seringkali menimbulkan kesulitan dalam perawatan dan dapat menimbulkan deformitas lengkung rahang. Penelitian ini bertujuan untuk mengetahui karakteristik fraktur palatum disertai fraktur dentoalveolar pada pasien trauma maksilofasial di Rumah Sakit Hasan Sadikin Bandung. Metode: Jenis penelitian observasional deskriptif dengan pendekatan cross-sectional da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This result is in accordance with previous studies which stated that 53% fell into minor category, 20% fell into moderate category, 11% fell into serious category, and the remaining percentages fell into heavy category. 18 According to the American Dental Association, oro-maxillofacial trauma emergencies can be potentially life-threatening. Therefore, they require immediate treatment to reduce severe pain and infection, and to stop ongoing tissue bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is in accordance with previous studies which stated that 53% fell into minor category, 20% fell into moderate category, 11% fell into serious category, and the remaining percentages fell into heavy category. 18 According to the American Dental Association, oro-maxillofacial trauma emergencies can be potentially life-threatening. Therefore, they require immediate treatment to reduce severe pain and infection, and to stop ongoing tissue bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…20 The authors found that the number of oro-maxillofacial trauma patients was inversely related to the evolution of the COVID-19 pandemic, with significantly fewer patients accessing hospital emergency rooms for dental care during the pandemic. 14,15,18,19 In times of the COVID-19 pandemic, with fewer available inpatient beds, data can be helpful for predicting the need for non-delayed hospital care for oral and maxillofacial surgery, and for managing hospital organizations to respond to reductions in surgical options; this was also reported in most countries in comparison to emergency procedures. 13,14,15 A medical literature shows how the pandemic outbreak had also caused patients to leave the hospital, possibly due to the fear of SARS-CoV-2 contact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations